Current measurement of engine oils under various voltage application - Amir Izzani, Mohamed; Benedick Conolius, Gabriel Addris; Norlin, Pauzi; Mohd Herwan, Sulaiman; Mohd Razali, Daud; Kadowaki, Kazunori (Springer Singapore, 2018)
This paper presents the conduction current measurement of engine oil of a vehicle during engine oil usage. A motorcycle and car engine oil is the sam-ple in this study. For motorcycle engine oil, sample was taken between 0km to 1500km while for car engine oil, it was taken between 0km and 9000km. The electrode was printed to PCB board and the oil was placed between electrode with 1mm gap. The current was measured by a microammeter under voltage ap-plied from 0.2 to 1.0kV. From the result it is understood that the current decreases with the increase in travelling distance of each vehicle. Motorcycle engine oil shows a higher current decreasing rate as compares to car engine oil.